Pulmonary arterial hypertension related to congenital heart disease with a left-to-right shunt: phenotypic spectrum and approach to management - Ferrero, Paolo; Constantine, Andrew; Chessa, Massimo; Dimopoulos, Konstantinos (Frontiers in Cardiovascular Medicine, 2024)
Patients with pulmonary hypertension associated with a left-right shunt include a wide spectrum of pathophysiological substrates, ranging from those characterized by pulmonary over-circulation to those with advanced pulmonary vascular disease. The former group may benefit from shunt repair in carefully selected cases but, when advanced pulmonary vascular disease has developed, defect closure should be avoided, and pulmonary vasodilators may be used to improve effort tolerance and hemodynamics. There is paucity of evidence, however, to support decision-making in the care of these patients.We discuss the principles of management in patients with pulmonary hypertension and a predominant left-right shunt. The recommendations and statements made in this paper are based on pathophysiological considerations and expert opinion.